Resistensi Malathion dan Aktivitas Enzim Esterase pada Populasi Nyamuk Aedes aegypti di Kabupaten Pekalongan - Dyah Widiastuti; Bina Ikawati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2016)
Pekalongan regency, Central Java (Indonesia) is one of area which experienced with Dengue Hemorrhagic Fever (DHF) incidence since many years ago. The extensive use of insecticides for dengue vector control has been carried out for long period in Pekalongan Regency. This fact stimulate the need to study the resistence status and esterase enzyme avtivity of Aedes aegypti to Malathion. The research was conducted in April-November 2014. Insecticide susceptibility assays were performed on F1 generation of wild-caught adult female Ae. aegypti mosquitoes from Simbangkulon Village Buaran Sub district, Kedungwuni Barat Village Kedungwuni Sub dsitrict and Karangsari Village Karanganyar Sub district, with the diagnostic doses of malathion (0,8%). Esterase enzyme activity of these mosquitoes was tested biochemically to find out the mechanisms of resistance to Malathion. Mosquitoes mortality as a result of Malathion effect showed variation in range from 3.33 to 13.75% in all study sites. That result indicated that Ae.aegypti mosquitoes are resistant to Malathion in all study sites . Based on biochemical assays, there was an increase if esterase enztyme activity of Ae aegypti in all study sites.. Therefore, alpha esterase enzyme activity could be associated with the mechanisms which responsible to malathion resistance in Ae. aegypti in Pekalongan. The results of this study provided the information about the malathion resistance status of Ae. aegypti in Pekalongan, and biochemical mechanisms which essential for monitoring the insecticide resistance in this area.